2021
DOI: 10.3389/fpls.2021.758976
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characteristics and Transcriptome of Cucumber Male Flower Development Under Heat Stress

Abstract: Cucumber (Cucumis sativus L.) is an important vegetable crop, which is thermophilic not heat resistant. High-temperature stress always results in sterility at reproductive stage. In the present study, we evaluate the male flower developmental changes under normal (CK) and heat stress (HS) condition. After HS, the activities of peroxidase (POD) and superoxide dismutase (SOD) and the contents of malondialdehyde (MDA) were increased. In addition, the pollen fertility was significantly decreased; and abnormal tape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 71 publications
1
19
0
Order By: Relevance
“…Then, the germinated seeds were cultivated in plant pots and grown in a growth cabinet. When the cucumber plants formed the sixth true leaves, they were moved into a phytotron with 70% relative humidity under normal conditions (CK, 12 h at 28°C in the light/12 h at 25°C in the dark) or high-temperature (HT, 12 h at 38°C in the light/12 h at 30°C in the dark) stress (Chen et al, 2021b). These temperature treatments were stopped until we collected enough male flowers for observations of the anther structure and pollen fertility and for the metabolomics experiments.…”
Section: Plant Materials and Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the germinated seeds were cultivated in plant pots and grown in a growth cabinet. When the cucumber plants formed the sixth true leaves, they were moved into a phytotron with 70% relative humidity under normal conditions (CK, 12 h at 28°C in the light/12 h at 25°C in the dark) or high-temperature (HT, 12 h at 38°C in the light/12 h at 30°C in the dark) stress (Chen et al, 2021b). These temperature treatments were stopped until we collected enough male flowers for observations of the anther structure and pollen fertility and for the metabolomics experiments.…”
Section: Plant Materials and Samplingmentioning
confidence: 99%
“…The investigation of pollen fertility was performed as previously described (Chen et al, 2021b). The mature male flowers were obtained and quickly put in Carnoy's solution (ethanol:acetic acid = 3:1) for over 24 h, and they were kept in 70% ethanol after washing three times.…”
Section: Cytological Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…The cucurbit model plant cucumber has been extensively studied to dissect the genetic architecture of important agronomic morphology (Pan et al, 2020a;Pan et al, 2020b;Chen et al, 2021;Shan et al, 2021). In addition to a large number of identified quantitative trait loci (QTLs) (Pan et al, 2020a;Wang et al, 2020), certain genes for corresponding traits, including fruit shape (Jiang et al, 2015;Xin et al, 2019;Zhao et al, 2019;Zhang et al, 2020b), inflorescence architecture (Wen et al, 2021), flowering time (Cai et al, 2020), plant height (Wang et al, 2017a) and stem diameter (Yang et al, 2022), have been characterized, which have considerably facilitated the genetic and molecular breeding of cucumbers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that high temperature inhibits the growth and development of cucumber plants, as indicated by inhibited the bioaccumulation, decreased chlorophyll content, increased the lipid peroxidation level, delayed flowering, and appeared dropping flower and fruit (Zhou et al, 2016;Wang et al, 2018a;Chen et al, 2021b). Cucumber plants have evolved a series of physiological and molecular mechanisms in response to high temperature stress, such as increasing the content of proline, activating antioxidant defense system, inducing the expression of heat shock proteins, and regulating plant hormone signal pathways (Wei et al, 2019; April 2022 | Volume 13 | Article 883876 Li et al miR9748 Mediates Thermotolerance via JA He et al, 2020;Chen et al, 2021b). Furthermore, calcium signal, transcription factors, and post-transcription regulation also mediate cucumber high temperature stress tolerance (Zhou et al, 2013;Xu et al, 2015;Yu et al, 2018;Wang et al, 2018bWang et al, , 2020a.…”
Section: Introductionmentioning
confidence: 99%